Control of the ICE-Harvest System using an Advanced Multi-Agent Framework - Fitzpatrick, Joshua (My University, 2022)
This thesis presents the development of an advanced control structure for the novel Integrated Community Energy and Harvesting (ICE-Harvest) system. The ICE-Harvest system is similar to a District Energy (DE) system in many ways and is different in others. It consists of a set of energy producing and storage units coupled to a thermal network which connects residential and commercial buildings of various types. Its operation is geared towards addressing challenges associated with the current energy landscape in Ontario, with potential to be applicable elsewhere in Canada. The control of this system is based on the implementation of a Multi-Agent System (MAS) combined with Sequential Logic Controllers (SLCs). Results demonstrate the capability of the developed control framework to operate the ICE-Harvest system while ensuring the thermal and electrical energy supply to the different consumers. Based on the results presented, the operation of the ICE-Harvest system by the developed control framework is compared with that of a Business-As-Usual (BAU) scenario. This comparison demonstrates the capability of the developed control framework to operate the ICE-Harvest system in a way that also increases the energy utilization and reduces emissions.